Synthesis and Antitumour Activity of Novel Colchicine C-10 Derivatives - Hong Shen, Li; Zhang, Le; Xian Wang, Hai; Wang, Xin; Jiao Zhang, Gai (Asian Journal of Chemistry, 2014)
A series of new colchicine C-10 derivatives (2a-i, 3a-h) were synthesized by replacement of the 10-methoxy with NR2 and SCH3 in order to determine their cytotoxic activity. The compounds were synthesized in good yield and the structures of all newly synthesized compounds were established on the basis of their IR, 1H NMR and elemental analysis. The synthesized compounds were tested in vitro antitumor activity against four human cancer cell lines by MTT assay. It was found that many of the derivatives displayed significant activity, particularly, compound 2a and 2b showed more potent cytotoxic activities than colchicine.